Place Attachment dan Intensi Berkunjung Kembali Konsumen pada Restoran Sunda - Tiannisabri, Meiya; Saphiranti, Dona (Serat Rupa: Journal of Design, 2024)
The increase in the number of restaurants in the city of Bandung comes from high market demand. These developments make Sundanese restaurants have to survive with a concept that has a local image from the trend of new concepts about places to eat in the city of Bandung. The attachment of place in residential areas to public space will be very different and more specifically if the public space is a type of restaurant that carries culture and uniqueness. Creation of a sense of location, belonging and connectedness to a place that engages the individual in an authentic way. This can generate positive emotions in users such as a unique sense of being bound, respected, respected and supported. These environmental conditions physically and socially will affect the user's activities to achieve and provide the user's destination to the place. Discussion of the concept of revisit intention with the phenomenon of consumer place attachment in Sundanese restaurants has never been discussed in previous research. It is hoped that this research will be useful for expanding knowledge of attached places and developing traditional themed restaurants, especially Sundanese restaurants. This study uses a correlational quantitative method which shows the relationship between variables with statistical data. This research focuses on determining the role of place attachment from functional, emotional, physical and social factors in Sundanese restaurants on consumers' intentions to revisit. The results showed that the form of the relationship between the independent variables was positive and unidirectional. The partial test results show that place identity does not have a significant positive influence on consumers' intention to revisit. The social factor of the place has a more significant influence, compared to other variables on the intention to return to the case study.